Improvement of Globalization Themes Learning Results in The Science Content Through The Blended Learning Learning Model - Anny Rahayu (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in science muple class VI elementary schools with the Blended Learning learning model with online PPT media with Zoom Meet. The research conducted was a Classroom Action Research (PTK) with three cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle the students who completed after carrying out the post test were 79%. In the second cycle students who completed after carrying out the post test were 88%. In the third cycle students who completed after carrying out the post test were 91%. These results indicate that the Blended Learning learning model can improve student learning outcomes, especially Class VI science muple at SDN 1 Magelung.